A study on the impact of social demographic factors on financial literacy among final year degree students in UiTM Seremban 3 / Hanif Imran Ahmad Rushdy and Muhammad Zaid Akmal Zainal - Ahmad Rushdy, Hanif Imran; Zainal, Muhammad Zaid Akmal (2022)
This study investigates the impact of social demographic factor on financial literacy among final year degree students in UiTM Seremban 3. This research used a convenience sampling involving 311 final year degree students in UiTM Seremban 3. This research is intended to establish the vital relationship between independent variables and dependent variables. This study indicates that the social demographic profile of gender, faculty, parental education and residency in finding the relationship with financial literacy. Financial literacy under this research is been viewed under three factors which are financial attitude, parental influence and financial knowledge. In this study, the survey approach of distributing online questionnaire was used to gather information and data in completing the discussion. Hence, the study of this research found that, residency and parental education plays a huge role in the determinant of student’s financial literacy. Therefore, this study suggested that more financial literacy programs can be conducted to younger students so that the student will have early awareness on the important of financial management.